APPLICATIONS OF THE SINE-GORDON EXPANSION METHOD TO THE SOME NONLINEAR PARTIAL DIFFERENTIAL EQUATIONS - SHAKIR, AZAD PIRO SHAKIR (Fırat Üniveristesi, 2016)
Bu çalışma dört bölümden oluşmaktadır. İlk bölümde, bu tezde kullanılan bazı temel tanım ve teoremler sunulmuştur. İkinci bölümde, Sine-Gordon Expansion metodunun genel özellikleri açıklanmıştır. Üçüncü bölümde, (2+1) boyutlu Zakharov-Kuznetsov denklemine, Benjamin–Bona–Mahony (BBM) denklemine, Equal width wave denklemine, modified Korteweg–de Vries (mKdV) denklemine Sine-Gordon Expansion metodu uygulanarak hiperbolik fonksiyon çözümleri, salınımlı dalga çözümleri elde edilmiştir. Ayrıca bu denklemlerin çözümlerinin iki ve üç boyutlu grafikler Wolfram Mathematica 9 programı kullanılarak çizilmiştir. Dördüncü bölümde, Sine-Gordon Expansion metodu ile elde edilen çözümler hakkında ayrıntılı sonuç verilmiştir.

This study consists four chapters. In the first chapter, we give some fundamental definitions and theorems which are necessary in this study. In chapter two, we present facts of the sine-Gordon Expansion Method. In chapter three, we apply the sine-Gordon Expansion Method to some know nonlinear solution equations, namely; (2+1)-dimensional Zakharov-Kuznetsov equation, Modified Benjamin-Bona-Mahony (mBBM) equation, Equal Width Wave equation, Modified Korteweg–de Vries (mKdV) equation. We obtain new solitary wave solution to the above mentioned models in form of hyperbolic function and trigonometric function solutions. All the computation in this study is carried out with Wolfram Mathematica 9. We verify all the obtained solutions and they indeed all satisfied their corresponding equations, we also plot the two-dimensional and three-dimensional graphics, all with help of Wolfram Mathematica 9. In chapter four the detailed conclusion about the results obtained by sine-Gordon Expansion Method has been given.
Sine-Gordon expansion metodunun bazı lineer olmayan kısmi differansiyel denklemlere uygulaması
Keywords: Matematik